2024
DOI: 10.1101/2024.04.11.24305657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the causal effect of placental physiology in susceptibility to mental and addictive disorders: a Mendelian randomization study

Pablo Jácome-Ferrer,
Javier Costas

Abstract: Background: Epidemiological studies have linked low birth weight to psychiatric disorders, including substance use disorders. Genomic analyses suggest a role of placental physiology on psychiatric risk. We investigated whether this association is causally related to impaired trophoblast function. Methods: We conducted a two-sample summary-data Mendelian randomization study using as instrumental variables genetic variants strongly associated with birth weight, whose effect is exerted through the fetal genome, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Transcriptome wide association studies (TWAS) identified 139 placenta schizophrenia-specific risk genes, and of those predicted to be upregulated in schizophrenia, there was significant enrichment for expression in EVTs 14 . Emerging evidence from Mendelian randomization supports a causal role of trophoblast physiology (and inflammation from fetal macrophages) in the development of offspring depression 23,24 . In particular, EVTs and villous cytotrophoblasts were significantly enriched for genes whose variants are associated with offspring depression, and hypoxia is a postulated mechanism 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome wide association studies (TWAS) identified 139 placenta schizophrenia-specific risk genes, and of those predicted to be upregulated in schizophrenia, there was significant enrichment for expression in EVTs 14 . Emerging evidence from Mendelian randomization supports a causal role of trophoblast physiology (and inflammation from fetal macrophages) in the development of offspring depression 23,24 . In particular, EVTs and villous cytotrophoblasts were significantly enriched for genes whose variants are associated with offspring depression, and hypoxia is a postulated mechanism 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from Mendelian randomization supports a causal role of trophoblast physiology (and inflammation from fetal macrophages) in the development of offspring depression 23,24 . In particular, EVTs and villous cytotrophoblasts were significantly enriched for genes whose variants are associated with offspring depression, and hypoxia is a postulated mechanism 24 . Cultured trophoblast cells exposed to hypoxia release factors into media that caused damage to neurons, including decreased dendrite length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation